A espacialização da luta das mulheres camponesas em Sergipe: feminismo e resistência - Santos, Laiany Rose Souza (2019)
This thesis aims to analyze the peasant women‘s fighting dynamics organized in over 105 groups in Sergipe‘s countryside, belonging to women‘s social movements, union‘s movements, mixed movements with women‘s and/or gender sectors in articulated or isolated forms. Such dynamics expresses that the rebellion is in the day‘s order. The Rural Territorial Development Public Policy (DTR) has been taken in its relation with Sergipe‘s agrarian issue and the peasant women‘s acting and their guidelines as structures in the participation type undertaken by them. It has been chosen the execution of a dialogue with the South Epistemologies, pointed by a third via whose narratives suggests giving voice to the subalterns, to the muted people in the history told by the dominants and with the Marxism, which analyses the society from the capitalist mode of production, in which the economic forces are preponderant constituted in the construction of the reality. Such dialogue is actualized in the thesis as a way to elucidate the object which is the organization of the peasant women. Nevertheless, we have chosen the historical dialectical materialism by the capital social metabolism and the inherent class struggle. It is considered that the apprehended must be used to explain the particular without losing sight of the totality, which presupposes that the subjects‘ voices must be exposed from its insertion in the social-historical context. Thus, yet the adopted theories in here belongs to distinct geographic places, they dialogue as they were/are subject to the hegemonic modernity/coloniality. The reflection over the Brazilian agrarian reality, as well as the women‘s struggle movement required to develop over the categories of space, territory and feminism from which it was possible to comprehend the unequal space production relations which puts the woman in a dominated space, charging the a political position front the power relation diversely manifested in the patriarchalism, machismo and class domination, taking them to the confrontation to the capital and to the State, since the countryside from the peasant feminism, as a strategy in the anticapitalistic struggle, approaching guidelines that reveal their demands and social conditions. This thesis aims to analyze the peasant women‘s fighting dynamics organized in over 105 groups in Sergipe‘s countryside, belonging to women‘s social movements, union‘s movements, mixed movements with women‘s and/or gender sectors in articulated or isolated forms. Such dynamics expresses that the rebellion is in the day‘s order. The Rural Territorial Development Public Policy (DTR) has been taken in its relation with Sergipe‘s agrarian issue and the peasant women‘s acting and their guidelines as structures in the participation type undertaken by them. It has been chosen the execution of a dialogue with the South Epistemologies, pointed by a third via whose narratives suggests giving voice to the subalterns, to the muted people in the history told by the dominants and with the Marxism, which analyses the society from the capitalist mode of production, in which the economic forces are preponderant constituted in the construction of the reality. Such dialogue is actualized in the thesis as a way to elucidate the object which is the organization of the peasant women. Nevertheless, we have chosen the historical dialectical materialism by the capital social metabolism and the inherent class struggle. It is considered that the apprehended must be used to explain the particular without losing sight of the totality, which presupposes that the subjects‘ voices must be exposed from its insertion in the social-historical context. Thus, yet the adopted theories in here belongs to distinct geographic places, they dialogue as they were/are subject to the hegemonic modernity/coloniality. The reflection over the Brazilian agrarian reality, as well as the women‘s struggle movement required to develop over the categories of space, territory and feminism from which it was possible to comprehend the unequal space production relations which puts the woman in a dominated space, charging the a political position front the power relation diversely manifested in the patriarchalism, machismo and class domination, taking them to the confrontation to the capital and to the State, since the countryside from the peasant feminism, as a strategy in the anticapitalistic struggle, approaching guidelines that reveal their demands and social conditions.